2016
DOI: 10.1159/000443014
|View full text |Cite
|
Sign up to set email alerts
|

Practical Considerations and the Intestinal Microbiome in Disease: Antibiotics for IBD Therapy

Abstract: The inflammatory bowel diseases, Crohn's and ulcerative colitis, have been treated with a range of antibiotics for inducing and maintaining remission, as well as the prevention of post-operative symptoms. To date, many studies have been performed assessing the efficacy of antibiotics when used alone, in combination with other antibiotics, or as an adjunctive therapy to other pharmaceutical treatments. Literature evidence supporting the use of antibiotics in IBD can be ambiguous, especially when considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…(61) Here, the use of tricyclic antidepressants was associated with a reduction in symptom burden in these patients. The intestinal microbiome is an attractive target for therapeutic intervention in IBD, and RCTs of antibiotics, (62) probiotics, (63) FMT, (64) and the low FODMAP diet, (65)(66)(67) have been conducted but, with the exception of the low FODMAP diet, these have largely focused on disease activity outcomes rather than IBS-type symptom reporting specifically. In one of these RCTs, (66) a significantly higher proportion of patients reporting IBS-type symptoms who were randomised to receive a low FODMAP diet achieved adequate relief of IBS-type symptoms than was observed in patients randomised to a control diet, with a number needed to treat of 3.…”
Section: Discussionmentioning
confidence: 99%
“…(61) Here, the use of tricyclic antidepressants was associated with a reduction in symptom burden in these patients. The intestinal microbiome is an attractive target for therapeutic intervention in IBD, and RCTs of antibiotics, (62) probiotics, (63) FMT, (64) and the low FODMAP diet, (65)(66)(67) have been conducted but, with the exception of the low FODMAP diet, these have largely focused on disease activity outcomes rather than IBS-type symptom reporting specifically. In one of these RCTs, (66) a significantly higher proportion of patients reporting IBS-type symptoms who were randomised to receive a low FODMAP diet achieved adequate relief of IBS-type symptoms than was observed in patients randomised to a control diet, with a number needed to treat of 3.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, numerous studies have tried to show a role for the gut microbiota in the development of CD. Indeed, it has been shown that a treatment with antibiotics such as ciprofloxacin or metronidazole is efficient to treat CD patients 38 . It has also been shown that antibiotic use in early childhood is a risk factor for inflammatory bowel disease development in adults 39 .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence supports that microbial imbalance in the GI tract influences the development and progression of IBD [61,[73][74][75][76][77][78][79][80]. Considering the key roles of the intestinal microbiota in the pathogenesis of IBD, the following theories have been postulated:…”
Section: Role Of the Microbiome In Ibd: Postulated Theoriesmentioning
confidence: 99%